Ex-MB leads Kedah honours list - News Straits, Times (New Straits Times, 2011)
ALOR STAR: Former Menteri Besar Datuk Seri Mahdzir Khalid heads the list of award recipients in conjunction with Sultan of Kedah Sultan Abdul Halim Mu’adzam Shah’s 83rd birthday celebrations today.